Grip force, EDL contractile properties, and voluntary wheel running after postdevelopmental myostatin depletion in mice - Personius, Kirkwood E. (American Physiological Society, 2010)
There is no consensus about whether making muscles abnormally large by reducing myostatin activity affects force-generating capacity or the ability to perform activities requiring muscular endurance. We therefore examined grip force, contractile properties of extensor digitorum longus (EDL) muscles, and voluntary wheel running in mice in which myostatin was depleted after normal muscle development. Cre recombinase activity was induced to knock out exon 3 of the myostatin gene in 4-mo-old mice in which this exon was flanked by loxP sequences (Mstn[f/f]). Control mice with normal myostatin genes (Mstn[w/w]) received the same Cre-activating treatment. Myostatin depletion increased the mass of all muscles that were examined (gastrocnemius, quadriceps, tibialis anterior, EDL, soleus, triceps) by ∼20–40%. Grip force, measured multiple times 2–22 wk after myostatin knockout, was not consistently greater in the myostatin-deficient mice. EDL contractile properties were determined 7–13 mo after myostatin knockout. Twitch force tended to be greater in myostatin-deficient muscles (+24%; P = 0.09), whereas tetanic force was not consistently elevated (mean +11%; P = 0.36), even though EDL mass was greater than normal in all myostatin-deficient mice (mean +36%; P < 0.001). The force deficit induced by eccentric contractions was approximately twofold greater in myostatin-deficient than in normal EDL muscles (31% vs. 16% after five eccentric contractions; P = 0.02). Myostatin-deficient mice ran 19% less distance (P < 0.01) than control mice during the 12 wk following myostatin depletion, primarily because of fewer running bouts per night rather than diminished running speed or bout duration. Reduced specific tension (ratio of force to mass) and reduced running have been observed after muscle hypertrophy was induced by other means, suggesting that they are characteristics generally associated with abnormally large muscles rather than unique effects of myostatin deficiency.